Women as a Force Multiplier for Bringing Nuclear Forensic Capabilities to the International Stage - Heather M Dion; Caterina Fox; Kim Knight; Anne Phillip (International Journal of Nuclear Security, 2023)
In 2009, the US Department of Energy National Nuclear Security Administration’s (NNSA’s) Defense Nuclear Nonproliferation Program initiated a new nuclear forensics outreach effort under its Confidence Building Measures Program. Little did they know that the timing could not have been better. This article focuses on the early years (2009–2015) of the NNSA’s international nuclear forensics outreach, specifically the efforts and experiences of the women who helped establish this program, building it from a fledgling, bilateral effort into an enduring technical capacity provider engaging with dozens of countries and multilateral organizations. At the onset of the program, nuclear forensics was an emerging priority within the US Government and receiving increased focus from international organizations through high-level diplomatic efforts such as the Nuclear Security Summit and Global Initiative to Combat Nuclear Terrorism. Additionally, working-level initiatives were gaining traction through the International Atomic Energy Agency and the Nuclear Forensics International Technical Working Group. Over the next 6 years, a small team comprising a uniquely large number of women NNSA federal, contract, and national laboratory staff served as key leaders engaging with the international community to strengthen global technical nuclear forensics capacity and best practices. The program continues today under the Nuclear Smuggling Detection and Deterrence Program as Investigation Support. The experiences shared here detail a unique time period when the new technical discipline of nuclear forensics was beginning to mature and gain international traction. The authors have made every effort to remember history correctly and be as inclusive as possible. A wealth of training, guidance, and exercise documentation was developed in the 2009–2015 time frame, much of which still serves as the foundation for today’s even more extensive program and community of dedicated technical and diplomatic practitioners.
Keywords: nuclear forensics; international capacity building